Pelatihan Pengelolaan Keuangan Sekolah dan E-Payment di SD Muhammadiyah 2 Krian - Imelda Dian Rahmawati; Alfan Rosyid; Kemil Wachida; Felsa Finda; Puput Melinda (Indonesian Journal Publisher, 2025)
The development of digital technology has penetrated all fields, including the world of education. This innovation and digitalization is something that SDM 2 Krian does not yet have. With 350 students currently, payments are made manually. This system results in errors in combining student payment reports. As a result, HR 2 Krian has not been able to present the school's financial reports. 2 Krian's HR financial sources still rely mostly on student revenues in the form of tuition fees and government BOS funds. For this reason, careful and professional financial management is needed to minimize the occurrence of financial errors that can lead to mismanagement, which can affect the quality of education and impact the school's reputation and achievements, both of which have a significant impact on public interest in registering their children. This activity aims to help resolve these problems, through mentoring activities and financial management training. This activity will also produce appropriate technology, namely the E payment application for cheaper and easier student tuition payments. The method of implementing community service uses socialization, training, application of technology, mentoring and evaluation as well as paying attention to the sustainability of this program. After implementing the training program and running the e-payment application, SD Muhammadiyah 2 Krian very openly accepted and responded well to the implementation of this program and continued it to improve financial services which had a positive impact on students and their guardians.